DINÂMICA DO FÓSFORO NA INTEGRAÇÃO LAVOURA-PECUÁRIA SOB SISTEMA PLANTIO DIRETO - Reifur, Hendrik Ivan (2011)
The necessity to preserve the soil, coupled with the constant search for lower production costs and increased productivity resulted in the use no-tillage (NT). Efficient technique in the preservation and use of highly weathered soils (tropical and subtropical soils). However, only the continuous cultivation of monocultures has been implicated in reduced profitability, rising the risks of production. Technique that increases profitability by the property maximizing, giving greater security product, is the crop-livestock integration (CLI).However, this technique uses the same area for plant and animal production. Even to achieve high yields in soils of low fertility under (CLI), requires the construction of fertility. So after correcting the acidity of these soils, the limiting factor becomes low levels of P in these soils. The objective of this study was to evaluate the feasibility of anticipated phosphate mineral fertilization in a succession of black oat (Avena strigosa Screb), maize (Zea mays L.) and annual ryegrass (Lolium multiflorum Lam) managed in CLI under NT. The experimental outline was randomized complete block with four repetitions of 10 treatments: T1 - without application of P (absolute control); T2-T4 – application of 60, 120 and 180 kg ha-1 P2O5 total, respectively, as triplo superphosphate (TSP); T5-T7 – application of 60, 120 and 180 kg ha-1 P2O5 total, respectively, in the form of rock phosphate (RP) Arad; T8-T10 – application of 60, 120 and 180 kg ha-1 P2O5 total, respectively in the form of magnesium thermophosphate (MPT). The plots received surface application (control, 60, 120 and 180kg ha-1 P2O5 total) as the sequence used. Before starting the experiment proceeded to the collection of soil layers (0-5, 5-10, 10- 15, 15-20 and 20-30 cm), and also during the cultivation of maize was collected samples for leaf diagnosis and nutrients accumulation. As for black oats and annual ryegrass was collected from plants in times of entry and exit of animals in the pasture (pre-and post-grazing pasture). However, analysis was performed to quantify the exportation of (N) nitrogen, (P) phosphorus and (K) potassium in the air part of forage due to the grazing animal. Yet been conducted evaluating the nutritional status of maize, the accumulation of (N, P and K), due to the application of phosphate fertilizers. After 12 months of surface application of phosphate sources and doses did not change soil acidity and the concentrations of Ca, Mg and S had little or no change. Although occurred effective for exchangeable K in the layers below 0-5 cm. The treatments increased the concentrations of P available by applying triple superphosphate (TSP) and thermophosphate magnesium (TPM), however the Mehlich-1 extractor overestimated P concentrated available. To the black oat export values of N,P and K were not affected by phosphate sources, except the P by applying TSP. The yield of black oats, maize grain and annual ryegrass had no effect posphosphate fertilizer, except for the application of MTP in the first pre-grazing. In the short term, it seems to be an interesting strategy for areas on NT that adopted CLI. It is concluded that the anticipated phosphate fertilizer surface can be made for maize in soils with high fertility, didn’t affecting in high yields.